Histopathological Aspects and Etiology of Pneumonias in Stranded Marine Mammals from Lima, Peru - Gonzales-Viera, Omar; Chavera, Alfonso; Yaipén-Llanos, Carlos; Perales-Camacho, Rosa (Brazilian Journal of Veterinary Pathology, 2011)
This study presents the histopathologic features of pneumonia in stranded marine mammals on the coast of Lima, Peru during the period of May 2003 to December 2008. Lung samples of 24 South American sea lions (Otaria flavescens), four bottlenose dolphins (Tursiops truncatus), one dusky dolphin (Lagenorhynchus obscurus), one Burmeister´s porpoise (Phocoena spinipinnis) and one marine otter (Lontra felina) were fixed in 10% formalin and then processed and stained with haematoxylin and eosin, periodic acid-Shiff (PAS) and trichromic of Masson. From the 31 samples collected only 29 were suitable for microscopic evaluation. The results show a rate of 29/29 pneumonias (100%), five of which were associated to parasites (17%), six of bacteria (21%), four of mixed (parasites and bacteria) (14%) and 14 were of nonspecific cause (48%). The present research indicates that those marine mammals from Lima, Peru are exposed to lungworms, flukes and bacteria that alone or mixed may cause pneumonias, which could be contributed or to be the primary cause of the stranding in these animals.